Inactivation of Prostaglandin E2 as a Mechanism for UGT2B17-Mediated Adverse Effects in Chronic Lymphocytic Leukemia - Allain, Eric P.; Rouleau, Michèle; Le, Trang; Vanura, Katrina; Villeneuve, Lyne; Caron, Patrick; Turcotte, Véronique; Lévesque, Eric; Guillemette, Chantal (Frontiers in Oncology, 2019)
High expression of the metabolic enzyme UDP-glucuronosyltransferase UGT2B17 in chronic lymphocytic leukemia (CLL) cells was associated with poor prognosis in two independent studies. However, the underlying mechanism remains unknown. We hypothesized that UGT2B17 impacts intracellular levels of hormone-like signaling molecules involved in the regulation of gene expression in leukemic cells. We initially confirmed in a third cohort of 291 CLL patients that those with high UGT2B17 displayed poor prognosis (hazard ratio of 2.31, P = 0.015). Consistent with the unfavorable prognostic significance of elevated UGT2B17 expression in CLL patients, high UGT2B17 expression was associated with enhanced proliferation of MEC1 and JVM2 malignant B-cell models. Transcriptomic analyses revealed that high UGT2B17 was linked to a significant alteration of genes related to prostaglandin E2 (PGE2) and to its precursor arachidonic acid, both in cell models and a cohort of 448 CLL patients. In functional assays, PGE2 emerged as a negative regulator of apoptosis in CLL patients and proliferation in cells models, whereas its effect was partially abrogated by high UGT2B17 expression in MEC1 and JVM2 cells. Enzymatic assays and mass-spectrometry analyses established that the UGT2B17 enzyme inactivates PGE2 by its conjugation to glucuronic acid (GlcA) leading to the formation of two glucuronide (G) derivatives. High UGT2B17 expression was further associated with a proficient inactivation of PGE2 to PGE2-G in CLL patient cells and cell models. We conclude that UGT2B17-dependent PGE2 glucuronidation impairs anti-oncogenic PGE2 effects in leukemic cells, thereby partially contributing to disease progression in high UGT2B17 CLL patients.